Analysis of the Impact of Organizational Culture, Employee Training, and Internal Communication on Employee Retention: A Case Study in the Manufacturing Industry in Indonesia - Hendriati, Yossi; Sufa, Siska Armawati; Telaumbanua, Eliagus; Uhai, Sabalius (IJBLE Scientific Publications Community Inc., 2024)
This research investigates the impact of organizational culture, employee training, and internal communication on employee retention within the Indonesian manufacturing industry. Using a mixed-method approach, data were collected from 179 employees across various manufacturing firms in Indonesia. The results reveal significant positive relationships between organizational culture, employee training, internal communication, and employee retention. A strong organizational culture, effective training programs, and transparent communication channels were found to enhance employee satisfaction, engagement, and commitment, ultimately reducing turnover rates. Practical implications suggest that manufacturing firms in Indonesia should focus on fostering a positive culture, investing in training and development, and improving communication to retain talent effectively. These findings contribute to understanding the dynamics of employee retention in the Indonesian manufacturing context and provide actionable strategies for organizations aiming to enhance retention efforts and sustain long-term success.